An Inkjet-printed Graphene Oxide–poly(3,4-ethylenedioxythiophene) poly(styrene sulfonate) Electrode for Nitrite Detection in Water - Putra, Budi Riza; Anindya, Weni; Rafi, Mohamad; Kartika, Ika; Thaha, Yudi Nugraha; Ridhova, Aga; Wahyuni, Wulan Tri (Makara Journal of Science, 2023)
In this study, a screen-printed electrode (SPE) for nitrite (NO2−) sensing was fabricated through an inkjet printing technique using a commercial printer machine and preparing an ink composite solution containing graphene oxide (GO) and poly(3,4 ethylenedioxythiophene) poly(styrene sulfonate) (PEDOT:PSS) as conductive materials. The optimum ink materials for SPE fabrication comprised GO and PEDOT:PSS with binders that resemble the viscosity of commercial ink. The surface topography of the fabricated SPE, which was characterized using scanning electron microscopy and atomic force microscopy, showed a smoother surface compared to the commercial screen-printed carbon electrode, with conductive ink materials deposited primarily from GO/PEDOT:PSS composites. This NO2− sensor exhibited a linear response at the concentration range of 50–1000 µM, with limit of detection and limit of quantification as 25 and 50 µM, respectively. In addition, the stability, reproducibility, and selectivity of this sensor presented acceptable values in the analytical range. Furthermore, the performance of this sensor was compared with that of a spectrophotometry technique using synthetic water samples, and the results revealed its good analytical recovery at a confidence interval of 95%. Thus, our sensor based on SPE-modified GO/PEDOT:PSS, fabricated via the inkjet printing technique, can be potentially applied in monitoring NO2− concentration in real samples.